2016 IEEE 23rd International Conference on Software Analysis, Evolution, and Reengineering (SANER) 2016
DOI: 10.1109/saner.2016.38
|View full text |Cite
|
Sign up to set email alerts
|

Localizing Multiple Faults in Simulink Models

Abstract: Abstract-As Simulink is a widely used language in the embedded industry, there is a growing need to support debugging activities for Simulink models. In this work, we propose an approach to localize multiple faults in Simulink models. Our approach builds on statistical debugging and is iterative. At each iteration, we identify and resolve one fault and re-test models to focus on localizing faults that might have been masked before. We use decision trees to cluster together failures that satisfy similar (logica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…We showed that the accuracy of our approach, when applied to Simulink models from the automotive industry, is comparable to the accuracy of statistical debugging applied to source code [42]. We further extended our approach to handle fault localization for Simulink models with multiple faults [41].…”
mentioning
confidence: 84%
“…We showed that the accuracy of our approach, when applied to Simulink models from the automotive industry, is comparable to the accuracy of statistical debugging applied to source code [42]. We further extended our approach to handle fault localization for Simulink models with multiple faults [41].…”
mentioning
confidence: 84%
“…SBFL has been recently employed to localize faults in Simulink/Stateflow CPS models [5,9,[19][20][21], showing similar accuracy as in the application to software systems [21]. The explanatory power of this approach is, however, limited, because it generates neither information that can help the engineers understand if a selected code location is really faulty nor information about how a fault is propagated across components.…”
Section: Related Workmentioning
confidence: 99%
“…The complexity of CPS models is manifold: these models typically combine discrete and continuous dynamics with an interplay between many variables, signals, state machines, look-up tables and components. Detecting problems in the early stages of CPS design [2,5,9,19,20] is of uttermost importance, before they propagate to the actual CPS with potentially catastrophic consequences.…”
mentioning
confidence: 99%
“…In terms of countries with high publications, we have identified that 37% of our primary studies were published from China, while 28% of the studies were from the United States (USA). However, countries like Singapore (24), Australia (15), and Portugal (12) are producing good papers out of 26 countries. Therefore, more effort is needed from other institutions in the rest of the countries to move the SFL research area forward in the near future.…”
Section: • the Most Frequently Used Fault Localisation Technique Is Sbflmentioning
confidence: 99%
“…In the last decades, various fault localisation techniques had been proposed with competing ways of effective fault identification [4,[6][7][8][9][10][11][12]. In a general sense, a fault localisation techniques assign suspicious scores to program statements that signify a statements degree of association with failure.…”
Section: Introductionmentioning
confidence: 99%